Pattern recognition in bioinformatics : 8th IAPR International Conference, PRIB 2013, Nice, France, June 17-20, 2013. Proceedings - Formenti, Enrico; Hao, Jin-Kao; Zhao, Xing-Ming; Laarhoven, Twan; Ngom, Alioune (Lecture Notes in Computer Science,, 2013)
This book constitutes the refereed proceedings of the 8th IAPR International Conference on Pattern Recognition in Bioinformatics, PRIB 2013, held in Nice, France, in June 2013. The 25 revised full papers presented were carefully reviewed and selected from 43 submissions. The papers are organized in topical sections on bio-molecular networks and pathway analysis; learning, classification, and clustering; data mining and knowledge discovery; protein: structure, function, and interaction; motifs, sites, and sequence analysis.